Development of Local Wisdom-Based E-Modules for Strengthening Education and Cultural Tourism in Tanah Toraja Regency - Suhendrik P; Rizal Arizaldy Ramly; Supardi Salam; Marwan Marwan; Irwan Irwan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to develop a Local Wisdom E-Module for senior high school students in Tanah Toraja Regency. It focuses on identifying students’ needs, designing the module, and evaluating its validity, practicality, and effectiveness before wider use. The study uses a Research and Development (R&D) approach with the 4-D model: defining, designing, developing, and disseminating. Data were collected through validation sheets, questionnaires, and pre- and post-tests. Results show the module achieved a validity score of 75%, indicating it is suitable for learning. Practicality testing revealed a very practical category with an average score of 3.32. Effectiveness testing showed improved student outcomes, with scores rising from 56.00 to 89.20. In conclusion, the e-module is valid, practical, and effective, and it also supports the integration of local cultural values into digital learning resources.